Wkład środowiska wielkopolskiego w rozwój patrologii - Czyżewski, Bogdan (Poznańskie Studia Teologiczne, 2020)
The proposed topic allows to learn about the scientific activity of the Wielkopolska researchers of the early Christian Church: Jan Sajdak (1882–1967), priest Józef Nowacki (1893–1964), priest Bronisaw Gadysz (1892–1943) and priest Ludwik Gadyszewski (1932–2009). They contributed to the development of patristics not only in Wielkopolska, but also in Poland and in the world. Wielkopolska is also associated with the Scriptures of the Fathers of the Church in which translations of writers of the first centuries of Christianity are published. Patrology textbooks have also been published. The most important of them was written by the priest Szczepan Piestoch and is intended especially for students of theology. Wielkopolska is also a Faculty of Theology which has been operating since 1998 at the University of Adam Mickiewicz University in Poznan. It includes the Department of Patristic Theology and currently the Department of Patristic Theology and Church History. Under the supervision of the faculty lecturers doctoral theses, master’s and bachelor’s the- ses, as well as monographs related to the period of Christian antiquity are prepared.